Influence of fiber volume fraction on the tensile properties and dynamic characteristics of coconut fiber reinforced composite - Zaman, Izzuddin (Penerbit UTHM, 2009)
The utilization of coconut fibers as reinforcement in polymer composites has been increased significantly due to their low cost and high specific mechanical properties. In this paper, the mechanical properties and dynamic characteristics of a proposed combined polymer composite which consist of a polyester matrix and coconut fibers are determined. The influence of fibers volume fraction (%) is also evaluated and composites with volumetric amounts of coconut fiber up to 15% are fabricated. In this work, the tensile test was carried out to determine the strength of material, while modal testing was used to obtain the dynamic characteristics of the composite material. Results were found that the strength of the composites tends to decrease with the amount of fiber, which indicates ineffective stress transfer between the fiber and matrix. The dynamic characteristic of composite was also having a same effect where the natural frequency decreased with increase of coconut fiber volume. However the damping ratio was found to be increased by the incorporation of fiber. When higher fiber content of 15% was used, the damping ratio shows the maximum value for almost all the frequency mode. It was observed that the effects of reinforcing polyester matrix with coconut fibers lead the composites more flexible and easy to deform due to high strain values and low stiffness. In fact, it may also be used to reduce high resonant effect.